A novel condom policy for young attenders at a sexual health clinic. Issue 4 (1st August 2001) - Wright, Simon; Tobin, Rose; Kell, Philip; Franks, Julia
Abstract : Objectives: To review the uptake of a new service for condom provision in the under 16s. Methods: A retrospective case note review of attenders at an inner London sexual health clinic. Results: The service was audited over a 3 month period in the spring of 2000. There were 97 individual attendances, 94% (92) male and 6% (5) female. 89% (87) had never attended a sexual health service before. When asked how they had heard of the clinic 88% (86) said a friend had told them about the clinic. 66% (64) claimed not to be sexually active. Conclusions: A novel policy of condom distribution to groups of boys has been successfully piloted at an inner London sexual health clinic. This policy appears to be overcoming the reluctance of teenage boys to access sexual health services.